Design solutions for nZEB retrofit buildings - Rynska, Elzbieta, 1962- (Engineering Science Reference, 2018)
"This book contains the outcomes and achievements of a project financed through Bilateral Cooperation Fund. It dwells on the nZEB approach to retrofit. It will allow a worldwide dissemination of knowledge attained during the KODnZEB - Project prepared within the framework of knowledge transfer: upgrade nZEB standard concept for two chosen buildings"--